Synthesis, Characterization and Biological Studies of S-1,3-Benzothiazol-2-ylthiophene-2-carbothioate and Its Ce(IV) and Nd(III) Complexes - Oruma, U.S.; Ukoha, P.O.; Asegbeloyin, J.N. (Asian Journal of Chemistry, 2014)
S-1,3-Benzothiazol-2-ylthiophene-2-carbothioate (SBC) was synthesized by the S-acylation of 2-mercaptobenzothiazole with thiophene-2-carbonylchloride in the presence of pyridine. Its Ce(IV) and Nd(III) complexes were also synthesized. The ligand and its Ce(IV) and Nd(III) complexes were characterized by UV-visible, IR and GC-MS spectroscopy. In addition, the ligand was characterized based on its 1H and 13C NMR data and the metal complexes based on conductivity measurement and stoichiometric ratio of combination. The infrared spectral study of S-1,3-benzothiazol-2-ylthiophene-2-carbothioate and its Ce(IV) and Nd(III) complexes gave evidence for coordination through the nitrogen of the benzothiazole ring and carbonyl oxygen. All the complexes were found to contain coordinated water and were assigned octahedral geometry. Antibacterial screening of the compounds were carried out in vitro on Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa). The compounds showed significant activities against Gram-positive bacteria than Gram-negative bacteria. However, the ligand showed more chemotherapeutic efficacy than the complexes. The compounds were not active against Pseudomonas aeruginosa.